2021
DOI: 10.3390/mi12010067
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Material Removal Mechanism and Effects of Machining Parameters during EDM of Zirconia-Toughened Alumina Ceramic

Abstract: Non-conductive structural ceramics are receiving ever-increasing attention due to their outstanding physical and mechanical properties and their critical applications in aerospace and biomedical industries. However, conventional mechanical machining seems infeasible for the machining of these superior ceramics due to their extreme brittleness and higher hardness. Electro discharge machining (EDM), well known for its machining of electrically conductive materials irrespective of materials hardness, has emerged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…It then cause the increase in circularity deviation, due to the occurrence of more sparks where the debris concentration are higher, which explain the dielectric breakdown easily occurs [45]. These results corroborate the findings of the previous work which found at higher peak currents, circularity increases, due to higher discharge energy which leads to bigger craters sizes [46]. Not only that, previous studies also found the effect of different dielectrics on the circularity at micro-EDM.…”
Section: Circularity Of the Holesupporting
confidence: 89%
“…It then cause the increase in circularity deviation, due to the occurrence of more sparks where the debris concentration are higher, which explain the dielectric breakdown easily occurs [45]. These results corroborate the findings of the previous work which found at higher peak currents, circularity increases, due to higher discharge energy which leads to bigger craters sizes [46]. Not only that, previous studies also found the effect of different dielectrics on the circularity at micro-EDM.…”
Section: Circularity Of the Holesupporting
confidence: 89%
“…In contrast to 3Y-TZP, the cracks were interconnected and those intergranular or transgranular cracks could facilitate the zirconia material removal during the sandblasting [ 31 ] as the particle size increased in 4Y or 5Y subgroups. The propagation of microcracks was oriented parallel to the surface and those lateral cracks were located up to 4.5 µm distance under the surface in 4Y or 5Y subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…However, researchers machined Al 2 O 3 -ZrO 2 using EDM by providing a very thin silver paint on its surface. [39] Some important applications of Al 2 O 3 -ZrO 2 ceramic composite are pump components, valve seats, bearing components, die inserts, etc. From Figure 1a, the XRD results show that Al 2 O 3 -ZrO 2 ceramic consists of alumina peaks and a small count of monoclinic zirconia with tetragonal zirconia phases.…”
Section: Materials Usedmentioning
confidence: 99%